A code-compliance framework for fire safety in student housing facilities. Issue 7 (8th May 2018) - Hassanain, Mohammad A.; Garkuwa, Jamilu A.; Sanni-Anibire, Muizz O.
Abstract : Purpose: The purpose of this paper is to present the development and implementation of a qualitative, code-compliance framework for property managers of student housing facilities. Design/methodology/approach: The paper identified the fire safety code requirements for student housing facilities and arranged these requirements in the form of a checklist, which was further validated by professional experts. Additionally, the paper presented an IDEF0 (Integrated Definition for Function Modeling) framework model that illustrates a stepwise process for the deployment of the checklist. A case study was conducted on three similar student housing facilities in a university campus to demonstrate the application of the framework. Furthermore, the findings from the case study were reported along with recommendations to improve the degree of compliance with the requirements of fire safety codes. Findings: The developed framework was validated by professional experts and through a case study. Fire safety provisions were mostly found to be adequate in the case study building. The authors proposed several actions to improve the current status of fire safety in the building. Originality/value: The paper serves to disseminate awareness about the occurrence of fires, their severe consequences and precautionary measures in student housing facilities. It also provides a standardized checklist for ease of use by property managers who may be unable to understand the technical terminologies found in fire safety codes and standards. Thus, the developed framework is of tangible value to property managers, building specialists and student housing administrators.